Razón neutrófilo-linfocito elevado como factor asociado a nefropatía diabética en pacientes con diabetes mellitus tipo 2 - De la Cruz-Hernández, Carlos Alonso (2024)
Objective: To identify the association between elevated neutrophil-lymphocyte ratio and diabetic nephropathy in patients with type 2 diabetes mellitus. Material and methods: An observational, analytical, cross-sectional study was conducted in a study sample of 206 diabetic patients attended at the Hospital Distrital El Esfuerzo de Florencia de Mora, Trujillo, Peru, during the period 2019-2022 who met the selection criteria. Patient information was collected in a card to be statistically analyzed. Results: Of the total 206 diabetic patients, 114 (55.3%) presented elevated neutrophil-lymphocyte ratio (NLR), having among them 77 (37.4%) with diabetic nephropathy and 37 (17.9%) without diabetic nephropathy; and, at the same time it was found that 92 (44.7%) did not present elevated neutrophil-lymphocyte ratio, having among them 17 (8.3%) with diabetic nephropathy and 75 (36.4%) without diabetic nephropathy, (p:0. 000), proving to be highly significant for the association between elevated neutrophil-lymphocyte ratio and diabetic nephropathy. Conclusion: Elevated neutrophillymphocyteratio is a factor associated with diabetic nephropathy in patients with type 2 diabetes mellitus.